HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PERILAKU PENCEGAHAN PENULARAN TUBERKULOSIS PARU PADA KELUARGA - Astuti, Erwin Puji; Ardianto, Ferry (Jurnal Penelitian STIKES Kediri, 2010)
ABSTRACT Â Lung Tuberculosis (Lung TBC) is a infection disease that need familyâ€™s role is very important to its prevention.Â The objective of this research is to analyze the relation between knowledge level and attitude with prevention behavior of to the spreading of lung tuberculosis (lung TBC) in the family in Work Region Public Health CenterÂ in North region ofÂ Kediri Town The design used in this research was correlational. The samples were 25 respondents and taken by Simple random Sampling. The independent variable the relation between knowledge level and attitudeÂ andÂ the dependent variable was behavior.Â Data were collected by questionnaire, then analyzed using Double Regression Test with the meaning level a < 0,05. The result of the research showed more than 50% respondents they were 14 respondents (56%) had good knowledge level and the majority respondents haveÂ good attitude they were 24 respondents (96%) and the most respondents have good and enough attitude were 11 respondents (44%). The result ofÂ Double Logistic Regression got p=0,253 where p>ï¡ so Ho was accepted, thus there is no relation between attitude and behavior. The conclusion of this research is that there is no relation between knowledge level and attitute with prevention behaviour of to the spreading of lung tuberculosis (lung TBC) in the family in Work Region Public Health CenterÂ in North region ofÂ Kediri Town Â Keywords : Knowledge, Attitude, Behavior, Lung Tuberculosis.